2020
DOI: 10.1186/s12958-020-00584-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cold stress on ovarian & uterine microcirculation in rats and the role of endothelin system

Abstract: Background: Cold, an environmental factor, induces many reproductive diseases. It is known that endothelin (ET) is a potent vasoconstrictor, and cold stress can increase the expression of ET and its receptors. The cold stress rat model was developed to examine two parameters: (1) the effects of cold stress on ovarian and uterine morphology, function, and microvascular circulation and (2) possible mechanisms of ET and its receptors involved in cold stress-induced menstruation disorders. Methods: The rat cold st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 50 publications
3
19
0
Order By: Relevance
“…The changes that occur in the POAT after browning and the effects of these changes on the peri-ovarian microenvironment, the ovarian microenvironment, and ovarian function have not been explored. We found that after POAT browning, the expression levels of APDN, Lep, and AMPK were significantly increased, similar to the effects observed during iWAT browning [ 9 , 32 ]. Our results suggested that the peri-ovarian microenvironment changes along with POAT browning.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The changes that occur in the POAT after browning and the effects of these changes on the peri-ovarian microenvironment, the ovarian microenvironment, and ovarian function have not been explored. We found that after POAT browning, the expression levels of APDN, Lep, and AMPK were significantly increased, similar to the effects observed during iWAT browning [ 9 , 32 ]. Our results suggested that the peri-ovarian microenvironment changes along with POAT browning.…”
Section: Discussionsupporting
confidence: 80%
“…Cold exposure has adverse effects on the female reproductive system [ 4 6 ], affecting ovarian [ 7 ] and uterine [ 4 ] functions and hormone secretion [ 8 ]. Possible reasons include: imbalance of ET-1 and its receptor expression leads to local tissue microvascular circulatory disturbances [ 9 ]; affects follicular development by activating sympathetic nerve activity in the ovary [ 10 , 11 ]; Cold stress can also cause reproductive hormone disorders, causing uterine arteries to contract, resulting in reduced blood flow [ 12 ]. However, the exact mechanisms through which these changes occur have not been well-elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that ET-1 is a local hormone whose secretion varies according to changes in the surrounding environment. Cold exposure increases the secretion of ET in plasma and increase in ET-1 in the heart tissue ( Chen and Sun, 2006 ; Barton and Yanagisawa, 2008 ; Wang D. et al, 2020 ). ET-1 plays an important role in the regulation of cardiac growth, myocardial contractility, and hemodynamics, and also leads to pathological myocardial hypertrophy by activating phosphoinositide 3-kinases (PI3Ks)/Akt pathway related to myocardial contractility and mitogen-activated protein kinase (MAPK)/extracellular signal-regulated kinases (ERK1/2) pathway related to cell hypertrophy ( Drawnel et al, 2013 ; Takano et al, 2020 ).…”
Section: Mechanism Of Myocardial Injury Induced By Cold Stressmentioning
confidence: 99%
“…It is also well-known that temperature alterations, either hot [ 37 ] or cold [ 11 ], cause adverse effects on the reproductive system. It has recently been reported that cold stress (0–1 °C) lengthened the estrous cycle in rats and reduced testosterone, E 2 , and progesterone levels, leading to reproductive organ dysfunction [ 38 ]. Additionally, restraint stress caused apoptosis in cumulus cells, reducing the oocyte developmental potential to the blastocyst stage [ 39 ].…”
Section: Discussionmentioning
confidence: 99%